Supply Chain Management and Value Added Analysis of Fish Raw Material in Restaurant Businesses in Pagimana District, Banggai Regency - Salista Husen; Fatlina Zainuddin; Asngadi Asngadi; Suryadi Hadi (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2026)
This study aims to analyze the performance of fish raw material supply chain management and the value added generated at each supply chain node in restaurants of Pagimana District, Banggai Regency. A qualitative descriptive approach was employed, with data collected through in-depth interviews, observation, and documentation involving 14 informants comprising restaurant owners, fishermen, collectors, retailers, and consumers. Data were analyzed thematically using a marketing margin approach to trace value-added distribution across supply chain actors. The results reveal that the fresh fish supply chain in Pagimana involves three to four key actors: fishermen, collectors/retailers, and restaurants. Each actor obtains a different margin: fishermen earn IDR 25,000/kg, collectors IDR 20,000/kg, retailers up to IDR 40,000/kg, and restaurants between IDR 16,000 and IDR 41,000 per portion depending on the purchasing channel. These findings imply the need to strengthen institutional coordination among actors to improve distribution efficiency and ensure more equitable value-added sharing along the local fishery supply chain.